1998
DOI: 10.1097/00001888-199802000-00023
|View full text |Cite
|
Sign up to set email alerts
|

Faculty appointment and tenure policies in medical schools

Abstract: The authors present recent data on changes under way in and the current status of faculty appointment and tenure policies in U.S. medical schools. The data are drawn from a survey conducted by the Association of American Medical Colleges in 1997, to which deans at all 125 U.S. allopathic medical schools responded, supplemented by follow-up telephone and electronic mail inquiries. Faculty evaluation systems and faculty compensation systems top the list of areas in which medical schools are most frequently makin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
43
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 0 publications
0
43
0
Order By: Relevance
“…1 The traditional "clinician-educator" role, 2,3 both in the classroom and in clinical settings, is still a significant component of an academic physician's career [4][5][6] . However, many administrative, research, scholarly, and advocacy-related roles are increasingly identified as important-if not mandatory-facets to an academic position in emergency medicine.…”
Section: Introductionmentioning
confidence: 99%
“…1 The traditional "clinician-educator" role, 2,3 both in the classroom and in clinical settings, is still a significant component of an academic physician's career [4][5][6] . However, many administrative, research, scholarly, and advocacy-related roles are increasingly identified as important-if not mandatory-facets to an academic position in emergency medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Emden (1998) highlighted that publishing in peer reviewed journals is an instrumental component in succeeding as a researcher. Productivity at this level will not only assist the academic with career advancement (Jones & Gold, 1998) but will also improve the standing of the department within the university and discipline (Baldwin & Chandler, 2002). This form of scholarly activity highlights the need to be open to, and accept constructive criticism or feedback through the process of peer review.…”
Section: University Of the Western Capementioning
confidence: 99%
“…[14] that financial pressures are causing medical schools to attempt to limit tenure, although it is unlikely to completely disappear. Indeed, Jones and Gold [15] note that only five of the 125 US medical schools fail to award tenure. (Six schools limit tenure to basic science faculty.)…”
Section: Potential Impact On Salaries and Tenure In Academic Medicinementioning
confidence: 99%